Flow-controlled expiration reduces positive end-expiratory pressure requirement in dorsally recumbent, anesthetized horses - Brandly, Jerrianne E.; Midon, Monica; Douglas, Hope F.; Hopster, Klaus (Frontiers in Veterinary Science, 2023)
Equine peri-anesthetic mortality is higher than that for other commonly anesthetized veterinary species. Unique equine pulmonary pathophysiologic aspects are believed to contribute to this mortality due to impairment of gas exchange and subsequent hypoxemia. No consistently reliable solution for the treatment of peri-anesthetic gas exchange impairment is available. Flow-controlled expiration (FLEX) is a ventilatory mode that linearizes gas flow throughout the expiratory phase, reducing the rate of lung emptying and alveolar collapse. FLEX has been shown to improve gas exchange and pulmonary mechanics in anesthetized horses. This study further evaluated FLEX ventilation in anesthetized horses positioned in dorsal recumbency, hypothesizing that after alveolar recruitment, horses ventilated using FLEX would require a lower positive end-expiratory pressure (PEEP) to prevent alveolar closure than horses conventionally ventilated. Twelve adult horses were used in this prospective, randomized study. Horses were assigned either to conventional volume-controlled ventilation (VCV) or to FLEX. Following induction of general anesthesia, horses were placed in dorsal recumbency mechanically ventilated for a total of approximately 6.5 hours. Thirty-minutes after starting ventilation with VCV or FLEX, a PEEP-titration alveolar recruitment maneuver was performed at the end of which the PEEP was reduced in decrements of 3 cmH2O until the alveolar closure pressure was determined. The PEEP was then increased to the previous level and maintained for additional three hours. During this time, the mean arterial blood pressure, pulmonary arterial pressure, central venous blood pressure, cardiac output (CO), dynamic respiratory system compliance and arterial blood gas values were measured. The alveolar closure pressure was significantly lower (6.5 +/- 1.2 vs 11.0 +/- 1.5 cmH2O) and significantly less PEEP was required to prevent alveolar closure (9.5 +/- 1.2 vs 14.0 +/- 1.5 cmH2O) for horses ventilated using FLEX compared with VCV. The CO was significantly higher in the horses ventilated with FLEX (37.5 +/- 4 vs 30 +/- 6 L/min). We concluded that FLEX ventilation was associated with a lower PEEP requirement due to a more homogenous distribution of ventilation in the lungs during expiration. This lower PEEP requirement led to more stable and improved cardiovascular conditions in horses ventilated with FLEX.